2013
DOI: 10.1353/jda.2013.0037
|View full text |Cite
|
Sign up to set email alerts
|

Do African Immigrants Enhance Their Home Nations’ Trade With Their Hosts?

Abstract: Employing data on the immigrant stocks of 43 African home countries who reside in 110 host countries and on trade flows between these countries during the year 2005, we examine whether African immigrants exert positive effects on their home countries' trade with the typical host country. Estimates from Tobit regression models indicate a one percent increase in the number of African immigrants in a given host country increases that country's exports to and imports from the typical home country by 0.132 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Controlling again for possible endogeneity biases, the 2SLS estimates show that coefficients are very similar to the benchmark 3SLS estimates. The insignificance of the trade–migration relationship confirms the hypothesis that the number of immigrants newly arrived in a country has to be sufficient to explain changes in trade (Tadesse & White, ).…”
Section: Robustness Checkssupporting
confidence: 70%
See 1 more Smart Citation
“…Controlling again for possible endogeneity biases, the 2SLS estimates show that coefficients are very similar to the benchmark 3SLS estimates. The insignificance of the trade–migration relationship confirms the hypothesis that the number of immigrants newly arrived in a country has to be sufficient to explain changes in trade (Tadesse & White, ).…”
Section: Robustness Checkssupporting
confidence: 70%
“…Migration inflows enter with a negative sign, implying that new migrants cause a decrease in exports to developing countries. According to Tadesse and White (), there is a threshold (a minimum number of migrants) beyond which migrants can trigger bilateral exports. Under this threshold, a negative effect can appear due to a loss of consumption in the migrant origin country.…”
Section: Resultsmentioning
confidence: 99%
“…Questioning the pro-trade effect of migrants, Parsons (2012) found that migration had a positive effect only on northern exports to the South. Finally, using cross-section data, Tadesse and White (2013) showed that African migrants significantly promoted African trade. However, their empirical approach does not control for the possible endogeneity of migration and they do not analyze the mechanisms through which African migrants could promote African trade.…”
Section: Review Of the Literaturementioning
confidence: 99%